First European quality of life survey quality of work and life satisfaction - Wallace, Claire; Pichler, Florian; Hayes, Bernadette C.; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
Assessing quality of life across Europe enables a comprehensive comparison to be made of countries that goes beyond narrow material considerations such as gross domestic product (GDP). Instead broader factors such as satisfaction with different aspects of life, as well as happiness in general are taken into account, (Noll, 2000; Noll and Zapf, 1994). Over the considerable length of time that quality of life has been studied, a wide variety of subjective and objective measures have been developed, covering a range of domains such as living standards, housing, health, family and social relationships, as well as work (Phillips, 2006; Rapley, 2003).
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Electronic books